Practice effects associated with repeated assessment of a clinical test of reaction time - Del Rossi, G.; Malaguti, A.; Del Rossi, S. (Journal of Athletic Training, 2014)
Context: Researchers have confirmed that the ruler-drop test could be included as part of a multifaceted concussion-assessment battery and potentially as a way to track recovery from head injury. However, it is unclear if this clinical test of reaction time would be characterized by inconsistent performance because of practice effects.